2017
DOI: 10.1145/3140582.3081040
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optimization for OpenCL programs on embedded heterogeneous systems

Abstract: Heterogeneous multi-core architectures consisting of CPUs and GPUs are commonplace in today's embedded systems. These architectures offer potential for energy efficient computing if the application task is mapped to the right core. Realizing such potential is challenging due to the complex and evolving nature of hardware and applications. This paper presents an automatic approach to map OPENCL kernels onto heterogeneous multi-cores for a given optimization criterion -whether it is faster runtime, lower energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
“…Predictive Modeling. Recent studies have shown that machine learning based predictive modeling is effective in code optimization [43], [44], performance predicting [45], [46], parallelism mapping [20], [47], [48], [49], [50], and task scheduling [51], [52], [53], [54], [55], [56]. Its great advantage is its ability to adapt to the ever-changing platforms as it has no prior assumption about their behavior.…”
Section: Domain-specific Optimizationsmentioning
confidence: 99%
“…More advanced models such as SVM classification has been used for various compiler optimisation tasks [46], [79], [80], [81], [82]. SVMs use kernel functions to compute the similarity of feature vectors.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…1) Static code features : Static program features like the number and type of instructions are often used to describe a program. These features are typically extracted from the compiler intermediate representations [46], [29], [52], [80] in order to avoid using information extracted from dead code. 2) Tree and graph based features : Singer and Veloso represent the FFT in a split tree [125].…”
Section: A Feature Representationmentioning
confidence: 99%